Baltic_salmon_baseline_data - Whitlock, Rebecca; Mantyniemi, Samu; Palm, Stefan; Koljenen, Marja-Liisa; Dannewitz, Johan; Ostergren, Johan (Dryad Digital Repository, 2017)
Baseline genotypes (17 microsatellite loci) for Baltic salmon from 27 stocks (3593 individuals of known stock of origin).